Synthesis and oxidation of some azole-containing thioethers - Potapov, Andrei S.; Chernova, Nina P.; Ogorodnikov, Vladimir D.; Petrenko, Tatiana V.; Khlebnikov, Andrei I. (Beilstein Journal of Organic Chemistry, 2011)
Pyrazole and benzotriazole-containing thioethers, namely 1,5-bis(3,5-dimethylpyrazol-1-yl)-3-thiapentane, 1,8-bis(3,5-dimethylpyrazol-1-yl)-3,6-dithiaoctane and 1,3-bis(1,2,3-benzotriazol-1-yl)-2-thiapropane were prepared and fully characterized. Oxidation of the pyrazole-containing thioether by hydrogen peroxide proceeds selectively to provide a sulfoxide or sulfone, depending on the amount of oxidant used. Oxidation of the benzotriazole derivative by hydrogen peroxide is not selective, and sulfoxide and sulfone form concurrently. Selenium dioxide-catalyzed oxidation of benzotriazole thioether by H2O2, however, proceeds selectively and yields sulfoxide only.
Keywords: azole; oxidation; sulfone; sulfoxide; thioether